MARITIME TRADE IN MAKASSAR IN THE XVI-XVII CENTURY - Sritimuryati, Sritimuryati; Suryaningsi, Tini (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This study aimed to describe the maritime trade in the half of XVI and XVII centuries. The method used was the historical method, namely heuristics, source criticism, interpretation, and historiography. Based on the study, it was found that Makassar traders played a central role in the archipelago maritime trade. The fall of Malacca Strait made Makassar as a new trading port that allowed the Makassar traders in a higher mobility. Makassar got a significant change as a trading center in the XVI century, previously in the XV century before becoming a trading center. Makassar traders established trade relations with foreign traders from Europe, China, India, and Arabic. The commodities traded were spices, textiles, and porcelain. The free trade policy at Makassar Port was a determining factor for the success of Makassar in attracting foreign traders to do their trading activities at Makassar Port.Â